Associations of pain intensity and pain‐related disability with psychological and socio‐demographic factors in patients with temporomandibular disorders: a cross‐sectional study at a specialised dental clinic. (30th January 2017) - Su, N.; Lobbezoo, F.; van Wijk, A.; van der Heijden, G. J. M. G.; Visscher, C. M.
Summary: The study assessed whether psychological and socio‐demographic factors, including somatisation, depression, stress, anxiety, daytime sleepiness, optimism, gender and age, are associated with pain intensity and pain‐related disability in patients with temporomandibular disorders (TMDs). In total, 320 TMD patients were involved in the study. The psychological status of each patient was assessed with questionnaires, including the Symptom Checklist‐90 (SCL‐90), Epworth Sleeping Scale (ESS), stress questionnaire and Life Orientation Test‐Revised (LOT‐R). TMD pain, including pain intensity and pain‐related disability, was assessed with characteristic pain intensity (CPI) and disability points scales. The associations of psychological and socio‐demographic factors with pain intensity and pain‐related disability were assessed through logistic regression analyses. Higher pain intensity was significantly associated with more severe anxiety ( P = 0·004), more severe somatisation ( P < 0·001), more severe depression ( P < 0·001), more severe stress ( P = 0·001) and lower optimism ( P = 0·025) in univariate regression analyses. However, multiple regression analysis showed that only somatisation was significantly associated with pain intensity ( P < 0·001). Higher pain‐related disability was significantly associated with more severe anxiety ( P < 0·001), more severe somatisation ( P < 0·001), more severe depression ( P < 0·001), more severe stress ( P < 0·001) and lower optimism ( P = 0·003) in univariate regression analyses. However, multiple regression analysis showed that only depression was significantly associated with pain‐related disability ( P = 0·003). Among the psychological and socio‐demographic factors in this study, somatisation was the best predictor of pain intensity, while depression was the best predictor of pain‐related disability.